2020
DOI: 10.21033/cfl-2020-443
|View full text |Cite
|
Sign up to set email alerts
|

Helping homeowners during the Covid-19 pandemic: Lessons from the Great Recession

Abstract: The Covid-19 public health crisis has sharply reduced the earnings of millions of U.S. households, following the severe curtailment of economic activity needed to contain the spread of the virus. Meanwhile, households continue to confront their ongoing financial obligations. The ability of households to manage these obligations has important consequences for the speed at which the U.S. economy can recover from the current crisis. Households that are wiped out financially in the coming months will not be in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In the USA, in the study conducted by Ettman et al (2021), it was found that citizens with fewer properties had higher exposure to financial stressors because of the pandemic and a higher prevalence of probable depression than persons with more properties. Also, Amromin (2020) opined that a wave of missed payments on mortgages could propagate a negative impact on the USA's financial system. The possible outcomes may frighten investors in the housing sector, weakening financial institutions and further prolong the economic slump if there is no significant intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, in the study conducted by Ettman et al (2021), it was found that citizens with fewer properties had higher exposure to financial stressors because of the pandemic and a higher prevalence of probable depression than persons with more properties. Also, Amromin (2020) opined that a wave of missed payments on mortgages could propagate a negative impact on the USA's financial system. The possible outcomes may frighten investors in the housing sector, weakening financial institutions and further prolong the economic slump if there is no significant intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Similar relief aids were provided during the great recession of 2007-2009 to mortgage borrowers in the form of acceptable long-term reductions in required payments (Amromin, Dokko & Dynan 2020). The reasons for the assistance provided were because of inadequate resources to make required payments and being in negative equity as a result of a decline in house values (Foote, Gerardi & Willen 2008).…”
Section: Pandemic Implications On Financial Behaviour and Related Rel...mentioning
confidence: 99%
“…The reasons for the assistance provided were because of inadequate resources to make required payments and being in negative equity as a result of a decline in house values (Foote, Gerardi & Willen 2008). During the great recession, homeowner assistance programmes were predominantly aimed at decreasing compulsory mortgage payments to meet a target paymentto-income ratio (Amromin et al 2020). However, for the COVID-19 pandemic, rapid and substantial liquidity support was required.…”
Section: Pandemic Implications On Financial Behaviour and Related Rel...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in March 2020, Los Angeles County in California promulgated nine public health orders, whereas Orange County, a neighboring county, implemented only four (Goldhaber-Fiebert et al 2021). Additionally, there is widespread county-level variation in the severity of COVID-19 infections and economic fallout (Aaronson and Alba 2020; Paul, Englert, and Varga 2021).…”
Section: Us Counties and Anti-asian Sentiment During Covid-19mentioning
confidence: 99%